Impact of Low-Level Viraemia on Virological Failure in HIV-1-Infected Patients with Stable Antiretroviral Treatment. Issue 4 (May 2016) - Navarro, Jordi; Caballero, Estrella; Curran, Adrian; Burgos, Joaquin; Ocaña, Inma; Falcó, Vicenç; Torrella, Ariadna; Pérez, Mercè; Ribera, Esteban; Crespo, Manuel
Background: Low-level viraemia (LLV) occurs in 20–40% of patients achieving viral suppression with antiretroviral therapy (ART). The risk of virological failure (VF: confirmed HIV RNA >200 copies/ml) in these patients is still a matter of debate. Methods: This is a prospective cohort study in HIV-infected adults attending the HIV clinic of a tertiary care hospital in Spain. Patients with HIV RNA <25 copies/ml and stable ART for at least 6 months presenting LLV (defined as HIV RNA between 25–1, 000 copies/ml) from January 2011 to January 2013 were included and followed until VF or end of follow-up in June 2014. Results: A total of 300 out of 1, 733 (17.3%) patients with undetectable viraemia for 4.2 years showed LLV: 25–50 copies/ml in 167 (55.7%) patients, 51–200 copies/ml in 111 (37%) and 201–1, 000 copies/ml in 22 (7.3%) cases. After a median follow-up of 2.6 years, 23 (7.7%) patients presented VF. No patient with a single or multiple unconfirmed LLV went on to develop VF. HIV RNA >200 copies/ml (HR 59.6; 95% CI 15.7, 227), ritonavir-boosted protease inhibtor (PI/r)-based dual therapy (HR 10.2; 95% CI 2.1, 49.8) and PI/r monotherapy (HR 7.9; 95% CI 1.4, 43.3) were associated with VF. Persistent LLV, defined as HIV RNA <200 copies/ml in at least three consecutive samples, for at least 12 weeks, was detected in 27 (1.6%) patients and 14 (51.9%) of those evolved to VF. Conclusions: Nearly one-fifth of patients on suppressive ART showed LLV and 8% of them developed VF. HIV RNA >200 copies/ml was the strongest predictor of VF. Over half of patients with persistent viraemia <200 copies/ml showed VF.